Identifikasi dan Pengaruh Peubah Penekan dalam Peningkatan Performa Mesin Mobil - Fauzhia Rahmasari; Fogot Endro Wibowo; Nur Witdi Yanto; Mareta Eko Pujiyanto (Jurnal Asiimetrik: Jurnal Ilmiah Rekayasa dan Inovasi, 2023)
One of the manufacturing companies in the automotive industry produces motor vehicle components, including engines. Compared to other spare parts, the engine plays a crucial role in vehicle operation. The primary purpose of the engine is to generate rotary power through the combustion of the air and fuel mixture contained within it. Therefore, optimal engine performance must be considered for the perfection of motorized vehicles, and external supporting factors that contribute to optimal engine performance must be identified. If this external supporting factor correlates with the used variables, it can be identified as a suppressor variable. A suppressor variable can improve engine performance by increasing the value of the coefficient of determination. The objectives of this study are to determine the type of suppressor variable and whether the suppressor variable can affect the performance of a car engine. According to the findings of this study, tire size (positive net suppression) and digital tuning (negative classical suppression) are suppressor variables that can influence the enhancement of automobile engine performance